Sanksi Pidana Terhadap Tindak Pidana Pembobolan Rekening Melalui Anjungan Tunai Mandiri (ATM) - Komang Saeramessatya Purwadi Sastra; I Nyoman Putu Budiartha; I Nyoman Gede Sugiartha (Jurnal Analogi Hukum, 2020)
The state of law requires that the law always be enforced, respected and obeyed by anyone without any reason for exclusion. Addressing this, positive law in Indonesia is required to respond to the crime phenomena committed by utilizing the technology. The problem of this study is 1) how is the arrangement of criminal Sanctions on the criminal act of account breach through the Mandiri Teller machine (ATM)? 2) What is the judge's consideration in discontinuing the account breach through the Mandiri Teller machine (ATM)? The research method used is a normative legal research method, with the literature study of primary and secondary legal materials. The results of the study can be concluded that: 1) the arrangement of criminal Sanctions on the criminal act of accounts breach through the Mandiri Teller (ATM) in the criminal CODE, LAW ITE, fund Transfer LAW, the anti-money laundering crimes ACT. 2) Judgment of the judges in the case of discontinuing the account breach through a automated teller machine (ATM) that the defendant TEGUH T KHASAN has been legally proven Hal-the thing that incriminated the defendant could be disturbing the community and could cause Harm to others, the things that lighten up, the defendant claimed to have never been punished, the defendant politely admitted and confessed frankly his deeds, the defendant felt guilty and regretted.